IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PADA PROGRAM KEMITRAAN PT. ANGKASA PURA II (PERSERO) CABANG PEKANBARU DALAM MENINGKATKAN KEBERHASILAN UMKM DI KOTA PEKANBARU - Rusdy Yanson; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Corporate social responsibility (CSR) is basically a need for corporations to interact with local communities. Corporate needs to adapt in order to get social benefits from their relationship with the local community, namely in the form of trust. In implementing CSR, a culture that is based on adaptive ethics is needed. This study aims to determine the implementation of Corporate Social Responsibility. PT. Partnership Program Angkasa Pura II (Persero) Pekanbaru Branch in Increasing the Success of UMKM in Pekanbaru City, knowing the mechanism for implementing the internal CSR partnership program of PT. Angkasa Pura II and knowing the implementation of the external CSR partnership program of PT. Angkasa Pura II (Persero) Pekanbaru Branch in increasing the success of UMKM. This study uses qualitative research methods using the Symmetrical Two Way Model. The research subjects consisted of 7 informants who were selected through a purposive technique. Data collection is done through interviews, observation and documentation. To do data analysis using interactive models Miles and Huberman. As well as checking the validity of the data using triangulation techniques The results of this study indicate the implementation of CSR in the PT. Angkasa Pura II runs smoothly starting from the initial concept of CSR in partnership programs specifically for UMKM players whose businesses are developing, have business licenses and are located in the city of Pekanbaru and its surroundings. First, the internal implementation mechanism of CSR on the PT. Angkasa Pura II in increasing success begins from the stage of submitting proposals by UMKM actors, then surveying the business location by the PKBL unit. Furthermore, after being accepted for the submission and decided to become a fostered partner, a loan agreement is signed from the UMKM actor and PT. Angkasa Pura II. Second, the external implementation mechanism of CSR in the PT. Angkasa Pura II in increasing success, will be conducted seminars and entrepreneurship training, mentoring and then some of the fostered partners will be included in exhibitions as promotional media in the city of Pekanbaru. The determinants of the success of the program are inseparable from local community support and community participation in this program. There were no significant obstacles in the implementation of the program but there were still people who did not know about this program.Keyword : Implementation, Corporate Social Responsibility, UMKM, Success